Determinants of inpatient satisfaction: evidence from Switzerland. Issue 1 (22nd December 2020) - Tobler, Stephan; Stummer, Harald
Abstract : Purpose: A common way to handle quality problems and increasing costs of modern health care systems is more transparency through public reporting. Thereby, patient satisfaction is seen as one main reported outcome. Previous studies proposed several associated factors. Only a few of them included organizational determinants with potential to inform the health care provider's management. Therefore, the aim of this study was to investigate the influence of organizational contingency factors on patient satisfaction. Design/methodology/approach: As a case, Switzerland's inpatient rehabilitation sector was used. Therein, a cross-sectional study of public released secondary data with an exploratory multiple linear regression (MLR) modeling approach was conducted. Findings: Five significant influencing factors on patient satisfaction were found. They declared 42.2% of the variance in satisfaction on provider level. The organizations' supplementary insured patients, staff payment, outpatients, extracantonal patients and permanent resident population revealed significant correlations with patient satisfaction. Research limitations/implications: Drawing on publicly available cross-sectional data, statistically no causality can be proved. However, integration of routine data and organization theory can be useful for further studies. Practical implications: Regarding inpatient satisfaction, improvement levers for providers' managers are as follow: first, service provision should be customized to patients' needs, expectations and context; second, employees' salary should be adequate to prevent dissatisfaction; third, the main business should be prioritized to avoid frittering. Originality/value: Former studies regarding public reporting are often atheoretical and rarely used organizational variables as determinants for relevant outcomes. Therefore, uniformed data are useful.